Influenza Evolution: New Insights into an Old Foe. Issue 6 (June 2017) - Moncla, Louise H.; Florek, Nicholas W.; Friedrich, Thomas C.
Abstract : Influenza viruses steadily evolve to escape detection by antibodies, necessitating vaccine updates. A new study uses a massively parallel approach, deep mutational scanning, to catalogue antibody escape mutations. This approach defines potential pathways of viral evolution, beyond those already observed in natural infections, and may help predict its future directions.